AB0825 Comparison of bone density changes one year after treatment with zoledronic acid verses daily teriparatide. (15th June 2017) - Aggarwal, AK; Jain, D; Aggarwal, N
Abstract : Background: The treatment of Osteoporosis is difficult to monitor and so usually incomplete resulting in inadequate response. 1 Objectives: To evaluate the minimum period of treatment required with Bisphosphonates and Parathyroid hormone in order to see a significant change in serial Bone Mineral Density analysis (BMD). Methods: Low BMD patients were subjected to yearly infusion of Zoledronic Acid 5mg (ZA) verses daily Subcutaneous injections of Teriparatide 20 μg (PTH). A single center pencil beam bone densitometer was used to measure serial BMD at baseline and yearly. Average BMD measures from the Spine L2, L3 and L4 (BS) and Total Hip (BH) were evaluated. The percentage change in the mean BS and BH readings was calculated to look for the least significant change (LSC) in the density scores. Results: Significant change of 4.65% was seen (LSC=2.6%) 2 in the Spine in the PTH group after one year of treatment while it took two years in the ZA group for a 2.77% change. There was no significant change (LSC=3.6%) 2 in both groups in the BH. A p>0.05 was considered statistically significant. The finding is summarized in Table 1 . Conclusions: Significant result of treatment with PTH requires a period of one year of therapy while with ZA it needs two years. The LSC in BMD is seen in the Spine and not in the Total Hip BMD. References: Glen M. Blake, Ignac Fogelman. Role of Dual-Energy X-Ray Absorptiometry in the Diagnosis and Treatment of Osteoporosis. Shepherd JA1, Lu Y. A generalized least significant change for individuals measured on different DXA systems. Disclosure of Interest: None declared